Tangential cathode magnetic field and substrate bias influence on copper vacuum arc macroparticle content decreasing; Surface and Coatings Technology; Vol. 306, Pt. A : Surface Modification of Materials by Ion Beams (SMMIB 2015) - Stepanov I. B. Igor Borisovich; Ryabchikov A. I. Aleksandr Ilyich; Ananin P. S. Petr Semenovich; Sivin D. O. Denis Olegovich; Shevelev A. E. Aleksey Eduardovich; Zhelomsky S. G. Sergey Gennadjevich (2016, 2016)
Title screen